Involvement of dopamine D2‐like receptors in the antiepileptogenic effects of deep brain stimulation during kindling in rats. (13th December 2022) - Rezaei, Mahmoud; Ghafouri, Samireh; Asgari, Azam; Barkley, Victoria; Fathollahi, Yaghoub; Rostami, Sareh; Shojaei, Amir; Mirnajafi‐Zadeh, Javad
Abstract: Aims: Deep brain electrical stimulation (DBS), as a potential therapy for drug resistive epileptic patients, has inhibitory action on epileptogenesis. In the present investigation, the role of dopamine D2 ‐like receptors in the antiepileptogenic action of DBS was studied. Methods: Seizures were induced in adult rats by stimulating the perforant path in a semi‐rapid kindling method. Five minutes after the last kindling stimulation, daily DBS was applied to the perforant path at the pattern of low frequency stimulation (LFS; 1 Hz; pulse duration: 0.1 ms; intensity: 50–150 μA; 4 trains of 200 pulses at 5 min intervals). Sulpiride (10 μg/1 μl, i.c.v.), a selective dopamine D2 ‐like receptor antagonist, was administered prior to the daily LFS application. Results: Kindling stimulations increased cumulative daily behavioral seizure stages, daily afterdischarge duration (dADD), and population spike amplitude (PS) in dentate gyrus following perforant path stimulation, while applying LFS decreased the kindled seizures' parameters. In addition, kindling potentiated the early (at 10–50 ms inter‐pulse interval) and late (at 150–1000 ms inter‐pulse interval) paired‐pulse inhibition and decreased the paired‐pulse facilitation (at 70–100 ms inter‐pulse interval). These effects were also inhibited by applying LFS. All inhibitory effects of LFS on kindling procedure were prevented by sulpiride administration. Conclusion: These data may suggest that LFS exerts its preventive effect on kindling development, at least partly, through the receptors on which sulpiride acts which are mainly dopamine D2 ‐like (including D2, D3, and D4 ) receptors. Abstract : Applying low‐frequency stimulation reduces kindling rate and prevents the kindling‐induced changes in field potential recordings. These effects are somehow through the receptors on which sulpiride acts which are mainly dopamine D2 ‐like (including D2, D3, and D4 ) receptors.